Blowup of Solution for a Class of Doubly Nonlinear Parabolic Systems. (18th November 2014) - Lu, Jun; Hu, Qingying; Zhang, Hongwei
Abstract : An initial boundary value problem for a class of doubly parabolic equations is studied. We obtain sufficient conditions for the blowup of solutions under suitable initial data using differential inequalities.